Case report: Refractory Evans syndrome in two patients with spondyloenchondrodysplasia with immune dysregulation treated successfully with JAK1/JAK2 inhibition - Gernez, Yael; Narula, Mansi; Cepika, Alma-Martina; Valdes Camacho, Juanita; Hoyte, Elisabeth G.; Mouradian, Kirsten; Glader, Bertil; Singh, Deepika; Sathi, Bindu; Rao, Latha; Tolin, Ana L.; Weinberg, Kenneth I.; et al. (Frontiers in Immunology, 2024)
Biallelic mutations in the ACP5 gene cause spondyloenchondrodysplasia with immune dysregulation (SPENCDI). SPENCDI is characterized by the phenotypic triad of skeletal dysplasia, innate and adaptive immune dysfunction, and variable neurologic findings ranging from asymptomatic brain calcifications to severe developmental delay with spasticity. Immune dysregulation in SPENCDI is often refractory to standard immunosuppressive treatments. Here, we present the cases of two patients with SPENCDI and recalcitrant autoimmune cytopenias who demonstrated a favorable clinical response to targeted JAK inhibition over a period of more than 3 years. One of the patients exhibited steadily rising IgG levels and a bone marrow biopsy revealed smoldering multiple myeloma. A review of the literature uncovered that approximately half of the SPENCDI patients reported to date exhibited increased IgG levels. Screening for multiple myeloma in SPENCDI patients with rising IgG levels should therefore be considered.